(untitled) (Materiali di Estetica. Terza serie, 2025)
The comparison between the meaning expressed by poetry and philosophy is understandable only in light of the fact that the two disciplines originate from a different structure of consciousness: that of the poet and that of the philosopher, who, while sharing the use of words and the modes of thought (rational and intuitive), organize it, in the specific disciplines, in a different way. However, poetry and philosophy also share something deeper that emerges from the heart of the analogy: the archetype, an immanent a priori structure, which underlies the dynamics of being, which cannot be rationalized and represented except through symbols. Investigated by psychology and philosophy as a pre-categorical structure, it takes on different names. As Vico suggests, it is present in symbolic form in myths and fairy tales as archaic sapiential knowledge. In philosophy, archetypes have been particularly valued by Hegel, among the best known, that assumed by the master-servant symbol. But both science and philosophy, in the search for truth and authenticity, cannot ignore such profound essences that are momentarily rationalized in the becoming, in the succession of theories and their re-elaborations. Poetry, on the other hand, does not try to explain the archetypes, but makes them live by involving the subject through multiple levels of consciousness, sensorial and conceptual, united in the unifying emotion of the same structure, perceived as a particular rhythmic and musical sense.